Reforming Islamic Education Management from Fazlur Rahman's Perspective: A Contextual Approach to Curriculum and Methods - Hidayah, Nur (CV. Tripe Konsultan, 2024)
Reforming Islamic Education Management through Fazlur Rahman's perspective is not only theoretical but also offers practical approaches that can be adapted by Islamic educational institutions. This study aims to examine the thoughts of Fazlur Rahman in the context of reforming Islamic education management, particularly in terms of curriculum and teaching methods. Fazlur Rahman is known as a modern Islamic thinker who emphasized the importance of a contextual approach in understanding Islamic teachings, including in the field of education. Through a qualitative approach with a literature study, this research explores the key concepts offered by Fazlur Rahman, such as double movement, the integration of revelation and reason, and the importance of social ethics in the educational process. The study's findings indicate that the reform of Islamic education management from Fazlur Rahman's perspective is a strategic effort to build a contextual, responsive, and relevant Islamic education system in line with the dynamics of the times. Fazlur Rahman strongly criticized the traditional Islamic education system, which he saw as textual and formalistic, arguing that such an approach has distanced education from its transformative goals. One of Rahman's major contributions is his emphasis on the integration of Islamic values and social reality in curriculum development. By promoting the double movement approach, Rahman offers a methodological framework for developing a curriculum that is not only text-based but also capable of addressing the actual challenges of the community's life. According to Rahman, the ideal curriculum is one that unites the dimensions of revelation and rationality, spirituality and knowledge, as well as the individual and society. Fazlur Rahman advocates for the transformation of the Islamic education curriculum so that it is not merely dogmatic, but capable of responding to the needs of the times and the challenges of modern society. Teaching methods, according to Fazlur Rahman, must be dialogical, critical, and based on a contextual understanding of the Qur'an and social reality. The implications of this thinking point to the need for a dynamic, adaptive, and orientation-focused Islamic education management system that aims to shape individuals who are both religious and rational.